Stringent control during carbon starvation of marine Vibrio sp. strain S14: molecular cloning, nucleotide sequence, and deletion of the relA gene. - Flärdh, K (1994)
In order to evaluate the role of the stringent response in starvation adaptations of the marine Vibrio sp. strain S14, we have cloned the relA gene and generated relaxed mutants of this organism. The Vibrio relA gene was selected from a chromosomal DNA library by complementation of an Escherichia coli delta relA strain. The nucleotide sequence contains a 743-codon open reading frame that encodes a polypeptide that is identical in length and highly homologous to the E. coli RelA protein. The amino acid sequences are 64% identical, and they share some completely conserved regions. A delta relA::kan allele was generated by replacing 53% of the open reading frame with a kanamycin resistance gene. The Vibrio relA mutants displayed a relaxed control of RNA synthesis and failed to accumulate ppGpp during amino acid limitation. During carbon and energy starvation, a relA-dependent burst of ppGpp synthesis concomitant with carbon source depletion and growth arrest was observed. Also, in the absence of the relA gene, there was an accumulation of ppGpp during carbon starvation, but this was slower and smaller than that which occurred in the stringent strains, and it was preceded by a marked decrease in the [ATP]/[ADP] ratio. In both the wild-type and the relaxed strains, carbon source depletion caused an immediate decrease in the size of the GTP pool and a block of net RNA accumulation. The relA mutation did not affect long-term survival or the development of resistance against heat, ethanol, and oxidative stress during carbon starvation of Vibrio sp. strain S14.